The relationship between Logic and Language in Al-Allamah al-Ḥillī’s believe - Karar Mahdy Abdulsahb– Ahmad Abdulsadeh Zweer ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
In My research paper I explain the relationship between Logic and Language in Al-Allamah al-Ḥillī’s believes, so the research divided as follow: First of all, the Introduction of the research, that it focuses on the important of the Subject and reason of choosing the subject and the details of the research. The first topic of the research, explain the definition of the Logic in language and Meaning from the different points of Logicians. The second topic of research, it focuses on the emergence of the Logic, and the results show that the Logic is found before Aristotle. In the third topic of research it focuses on the definition of the linguistics in the language and meaning. The fourth topic deals with some of the essential ideologies that mentioned about the essential the language. The fifth topic it concerns to the function of the language. The sixth topic it concerns on the relationship between Logic and language, the differences and the power of concern between them. At the end the research concerns with the results that the researcher found them in his investigation.